Parliamentary dawn: The new self-confidence of the European Parliament - Daniela Kietz; Nicolai von Ondarza (Stiftung Wissenschaft und Politik (SWP), 2010)
The European Parliament is one of the greatest beneficiaries of the Treaty of Lisbon. In the recent series of confrontations it has surprised member states by taking a combative stance and has established itself as a force to be reckoned with. The member states must quickly adjust to the new set of rules and a Parliament that vehemently demands its right to actively participate in all EU policy areas while not refraining from resorting to power politics. Otherwise there is a real danger that the EU's ability to act will be undermined. Likewise, parliamentarians will have to learn to use their new powers carefully and responsibly. If the Parliament, however, wishes to live up to its ambition of being on equal footing with the member states when forming and framing European policy, one of its greatest challenge lies in moving beyond simple legislation and having an active impact on the setting of long-term political agendas. More than ever, these are set by the heads of state and government in the European Council
Keywords: 320